2008
DOI: 10.1088/0957-4484/19/22/225605
|View full text |Cite
|
Sign up to set email alerts
|

PbTiO3nanorod arrays grown by self-assembly of nanocrystals

Abstract: Arrays of ferroelectric lead titanate (PbTiO(3)) nanorods have been grown on a substrate by a novel template-free method. Hydrothermal treatment of an amorphous PbTiO(3) precursor in the presence of a surfactant and PbTiO(3) or SrTiO(3) substrates resulted in the growth of PbTiO(3) nanorod arrays aligned perpendicular to the substrate surface. Two steps in the growth mechanism were demonstrated: first an epitaxial layer was formed on the substrate; this was followed by self-assembly of nanocrystals forming a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 49 publications
2
27
1
Order By: Relevance
“…[90] The lower part of the mesocrystal layer is relatively porous, the middle part more dense, and the surface part consists of nanorods growing along the polar [001] direction. The PbTiO 3 rods with tetragonal phase have a square cross-section of 35-400 nm and length up to 5 mm.…”
Section: Ferroelectric Lead Titanate (Pbtio 3 )mentioning
confidence: 99%
“…[90] The lower part of the mesocrystal layer is relatively porous, the middle part more dense, and the surface part consists of nanorods growing along the polar [001] direction. The PbTiO 3 rods with tetragonal phase have a square cross-section of 35-400 nm and length up to 5 mm.…”
Section: Ferroelectric Lead Titanate (Pbtio 3 )mentioning
confidence: 99%
“…Some studies have shown that 1D nanocrystals aligned vertically on a selected substrate can also be synthesized by the hydrothermal method. 4,[7][8][9][10] For some cases the substrate surfaces should be chemically modified; for instance, vertically aligned PZT nanorods with a hexagonal cross-section were grown on a TiO 2 -coated Ti foil. 7 Potassium sodium niobate ((K,Na)NbO 3 , abbreviated as KNN hereafter) is one of the most potentially useful candidates for lead-free ferroelectrics, 11,12 and has attracted increasing attention as a high-performance piezoelectric ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Nowadays, with a shrinking of device size to the nanoscale, ferroelectric oxides nanostructures have become the focus of numerous investigations. [6][7][8][9][10][11] In particular, one-dimensional (1D) ferroelectric nanostructures, including nanorods, [12][13][14] nanowires, [15][16][17][18] nanotubes, 7 nanobelts 19 and nanofibers 20,21 have attracted worldwide attention due to their unique piezoelectric and ferroelectric properties compared to those of bulk and film counterparts in the last decade. 8,15,16,19,22 It has been demonstrated that increasing the aspect ratio and partial substitution could improve their ferroelectric and piezoelectric properties and facilitate their potential application in sensors and generators.…”
Section: Introductionmentioning
confidence: 99%